2010
DOI: 10.4161/cc.9.15.12381
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol enhances gemcitabine antitumor activity in vitro and in vivo by promoting apoptosis in a human pancreatic carcinoma model system

Abstract: (2010) Calcitriol enhances gemcitabine antitumor activity in vitro and in vivo by promoting apoptosis in a human pancreatic carcinoma model system, Cell Cycle, 9:15, 3094-3101,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…[2][3][4] At the cellular level, 1,25(OH) 2 D 3 modulates proliferation, differentiation, survival, metabolism and physiology and potentiates the antitumoral activity of certain chemotherapeutic agents in a celltype-and -context-dependent manner. [5][6][7][8][9][10] According to the classical model of action, 1,25(OH) 2 D 3 binds to and activates a transcription factor of the nuclear receptor superfamily, the vitamin D receptor (VDR), and modulates the transcription rate of its target genes. 11 1,25(OH) 2 D 3 is a major regulator of gene expression in higher organisms, as VDR is expressed in at least 38 human cell types.…”
mentioning
confidence: 99%
“…[2][3][4] At the cellular level, 1,25(OH) 2 D 3 modulates proliferation, differentiation, survival, metabolism and physiology and potentiates the antitumoral activity of certain chemotherapeutic agents in a celltype-and -context-dependent manner. [5][6][7][8][9][10] According to the classical model of action, 1,25(OH) 2 D 3 binds to and activates a transcription factor of the nuclear receptor superfamily, the vitamin D receptor (VDR), and modulates the transcription rate of its target genes. 11 1,25(OH) 2 D 3 is a major regulator of gene expression in higher organisms, as VDR is expressed in at least 38 human cell types.…”
mentioning
confidence: 99%
“…It is known that calcitriol has antiproliferative activity through different mechanisms such as cell cycle arrest and apoptosis (38)(39)(40)(41). Additionally, calcitriol can enhance anti-cancer activity of anti-cancer drugs including gemcitabine (42) and paclitaxel (43) both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Mechanisms of GMT-mediated apoptosis have been investigated in several cancers. [28][29][30][31] GMT has been increasingly used to treat hepatobiliary cancers because of its reasonable efficacy for treating pancreatic cancer. 32 Low dose of GMT is preferred to avoid severe toxicity, especially pulmonary toxicity.…”
mentioning
confidence: 99%
“…6,[20][21][22][23][24][25] Based on previously published data, TMX and GMT appear to induce apoptosis via distinct mechanisms. 11,13,[28][29][30][31] Therefore, we evaluated the efficacy of combination therapy with TMX and GMT on human cholangiocarcinoma tumorigenesis in a mouse xenograft model and investigated the responsible molecular mechanisms. We have found that TMX and GMT induce apoptosis and inhibit cholangiocarcinoma tumorigenesis.…”
mentioning
confidence: 99%